Metabolic profiles, energy expenditures, and body compositions of the weight regain versus sustained weight loss patients who underwent Roux-en-Y gastric bypass - Prapimporn Chattranukulchai Shantavasinkul (2022)
Background: Weight regain (WR) has been an emerging problem after Roux-en Y gastric bypass (RYGB) and little is known about the mechanisms of WR after RYGB. Objective: To evaluate the mechanisms of WR after RYGB through the postprandial gut hormones response, particularly glucagon-like peptide-1 (GLP-1), which regulates appetite control, energy expenditure, body composition, physical activities, dietary intake, and psychological factors. Setting: Duke University Medical Center, Durham, North Carolina. Methods: A cross sectional study of 34 patients who underwent RYGB at least 2 years and achieved ≥50% of excess weight loss at 1year was conducted. The subjects were categorized into WR group or sustained weight loss group, based upon whether their WR was ≥15% of postoperative lowest weight. Results: The WR group had less augmented postprandial GLP-1 response but exaggerated hyperinsulinemia. Postprandial peptide YY, ghrelin, and glucose were not different between group. Patients who regained weight required less weight-adjusted energy expenditure and had more percentage body fat and less percentage lean mass. The caloric intake and diet composition were comparable between groups; however, the WR group had higher depression scores, binge eating scales, and hunger rating and spent significantly less time on vigorous exercise. Conclusions: The mechanisms of WR in patients who were initially successful after RYGB are complex and involved not only the role of postprandial gut hormone response but are also related to energy expenditure adaptation and body composition changes. Moreover, food preference and physical activity may play roles in weight control after bariatric surgery. Further prospective controlled trial is needed to explore the mechanisms of WR.